x = +1/2 and x = -2/3
6x^2 + x = 2 can be made into a quadratic equation by subtracting "2" from each side: 6x^2 + x - 2 = 0. Then just substitute into the quadratic equation solution "{ -b +/- (b^2 - 4ac)^(0.5) } / 2a" which is much faster than trying to mess around factoring or completing squares when your "x^2" coefficient is not 1.
Substituting gives us x = +1/2 and x = -2/3. So if you had factored, you would have gotten: (2x - 1)*(3x + 2) = 0 and you would have solved from there.
2007-08-27 08:40:01
·
answer #1
·
answered by bimeateater 7
·
0⤊
0⤋
I'm not a math Wise but this may help you
Look at 6 time x^2 + x = 2
Move these terms to the left -2
It becomes 6 times x^2 + x -2 =0
or
Look at 6 Times x^2 +x -2 =0
6time x^2 + x -2 =0 is a quadratic: 6*x^2+x-2 =0, and has solutions 0.5,-0.666666666666667
It becomes 0=0
Results 0=0
Solution: X=0.5 X^2 = 0.6666666666667
Done!
I hope this help.
Remember Cheeting is not the key so make sure you try it first and then check your anwser....That is what I would do. Also if you not getting the material check with your teacher for addition help.
Try the web site listed below for help as well.
2007-08-27 16:09:28
·
answer #2
·
answered by LeeLee 1
·
0⤊
1⤋
6x² + x - 2 = 0
(3x + 2) (2x - 1) = 0
x = - 2 / 3 , x = 1 / 2
2007-08-27 17:48:13
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
6x^2 + x = 2
= 6x^2 + x - 2 = 0
6x^2 + 4x - 3x - 2 = 0
2x(3x + 2) - 1(3x + 2) =0
(2x - 1)(3x + 2) = 0
so 2x = 1 or
3x = - 2 = 0
so x = 1/2 or -2/3
2007-08-27 15:38:36
·
answer #4
·
answered by mohanrao d 7
·
0⤊
0⤋
6x^2 + x = 2
6x^2 + x - 2 = 0
(3x + 2)(2x - 1) = 0
x = -2/3, x = 1/2
The hard part is finding the factors (3x + 2)(2x - 1)
You can do it by trial and error, but see also the lesson at the lnk below
2007-08-27 15:39:35
·
answer #5
·
answered by kindricko 7
·
1⤊
1⤋
6x² + x = 2
6x² + x -2=0
(2x-1)(3x+2)=0
x=1/2, -2/3
or use the quadratic equation which is:
(-b+/-âb²-4ac) ÷ 2a
for: a²+2b+c²
plug in the equation.
6x² + x -2 =
(-1+/-â1+48) ÷ 12
(-1 +/- 7) ÷ 12
x= -2/3, 1/2
BOTH ARE CORRECT!
2007-08-27 15:32:08
·
answer #6
·
answered by Anonymous
·
0⤊
2⤋
set the equation equal to zero, so subtract 2 from both sides. you get 6x^2 +x - 2 = 0
Then solve for x, use quadratic equation to solve.
2007-08-27 15:34:08
·
answer #7
·
answered by Shredded Cottage Cheese 6
·
0⤊
0⤋
6x^2+x-2=0
6x^2 + 4x - 3x - 2 = 0
2x(3x+2)-(3x+2)=0
(3x+2)(2x-1)=0
x=-2/3, or x=1/2
2007-08-27 15:33:01
·
answer #8
·
answered by de4th 4
·
0⤊
0⤋
6x^2 + x - 2 = 0
(3x + 2) (2x - 1) = 0
x = -2/3, 1/2
PS: Kindricko, thanks for that link!
2007-08-27 15:40:04
·
answer #9
·
answered by hznfrst 6
·
0⤊
0⤋
6x^2+x-2=0
6x^2 + 4x - 3x - 2 = 0
2x(3x+2)-(3x+2)=0
(3x+2)(2x-1)=0
x=-2/3, or x=1/2
2007-08-27 15:31:39
·
answer #10
·
answered by god knows and sees else Yahoo 6
·
1⤊
2⤋